(3QSGdI aj GdSdhcs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hGgH GdYbd heHOYg hfGUH Gdfbd hTQYg GdPj NUU ChdjGFg HETQGa CfhGQg s
(3BNQgG (B:s
(3adeKd gPG adjYed GdYGedhf haj eKd gPG adjJfGaS GdoeJfGaShf hGdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi SjOfG eMeO hYdi Bdg hUMHg CLeYjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdMGL YHOGdeLjO Thbj HcQj (B((3GdehUd (B1/1) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs